Zambia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper presents an analysis of change in Zambia's mining fiscal regime. Foreign investment has revived Zambia's mining sector. However, its mining sector's direct contribution to government revenues has been low. Reflecting persistent concerns about the low contribution of the mining sector to budget revenues, the government has amended the fiscal regime many times over the last seven years. The 2015 budget introduced major changes to the mining fiscal regime. The authorities estimate that the change would boost budget revenues from the mining sector by about 1 percent of GDP, based on an assumption that the change would have no adverse impact on production.